Apple Maggot, Apple Maggot Fly, Rhagoletis pomonella (Walsh) (Insecta: Diptera: Tephritidae) - Howard V. Weems; Thomas R. Fasulo (EDIS)
Revised! EENY-261, a 4-page illustrated fact sheet by H. V. Weems, Jr. and T. R. Fasulo, is part of the Featured Creatures collection. It describes this primary pest of cultivated apples, especially in the northeastern United States and southeastern Canada, with a range extending into central Florida — synonym, distribution, description, life history and habits, hosts, damage, and management. Includes references. Published by the UF Department of Entomology and Nematology, December 2009.